Corporations compassion culture : leading your business toward diversity, equity, and inclusion - Schreane, Keesa C. (John Wiley & Sons, Inc., 2021)
"In the past year, corporations have been moving to having a diversity and inclusion program. Diversity refers to the traits and characteristics that make people unique and inclusion refers to the behaviors and social norms that ensure people feel welcome The manner in which corporations are run globally is over. The author examines how corporations worldwide have failed when it comes to inclusion and gender equality and provides ideas on how businesses can address these issues."--